2012
DOI: 10.1007/s00586-012-2328-6
|View full text |Cite
|
Sign up to set email alerts
|

Loading rate patterns in scoliotic children during gait: the impact of the schoolbag carriage and the importance of its position

Abstract: Purpose Concerns have been raised regarding the effects of schoolbag carriage on adolescent schoolchildren and particularly those with a pre-existing spinal deformity. The purpose of this study was to determine the effect of school backpack loads in scoliotic and healthy school-age children during walking, in terms of peak vertical ground reaction forces and loading rates. We hypothesized that walking with a loaded backpack would have a greater effect on gait kinetics of scoliotic compared to healthy. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…Unele studii [10][11][12][13][14][15] au raportat, de asemenea, cã o presiune plantarã mai mare la nivelul antepiciorului ar putea mãri ºansele de apariþie a deformãrilor de tip varus sau valgus atunci când copiii merg cu ghiozdanul în spate. Meng Zhaoli ºi colab.…”
Section: Discuþiiunclassified
See 1 more Smart Citation
“…Unele studii [10][11][12][13][14][15] au raportat, de asemenea, cã o presiune plantarã mai mare la nivelul antepiciorului ar putea mãri ºansele de apariþie a deformãrilor de tip varus sau valgus atunci când copiii merg cu ghiozdanul în spate. Meng Zhaoli ºi colab.…”
Section: Discuþiiunclassified
“…Studies [10][11][12][13][14][15] also reported that a larger plantar pressure loaded on forefoot could cause an increased possibility of varus or valgus deformity when children walked carrying schoolbag. Whereas, Meng Zhaoli et al [10] studied the plantar pressure distribution of school-aged children with different schoolbag weights, and their results implied that the peak pressure under 2nd and 3rd metatarsals increased with 4 kg bags weight bearing whilst normal walking and the center of pressure vibrated a lot in the medial-lateral direction; besides, they also suggested that possibility of varus or valgus deformity was high as the schoolbag weight increased.…”
Section: Discuþiimentioning
confidence: 99%
“…In this way, high GRFs have been associated with injuries at the spine level [25] and with lower-limb injuries [23], inducing degradation of the biomechanical properties of the joint cartilage. Mechanical forces influence vertebral growth [26], and high loading rates may have negative effects on bone health [27,28]. In this sense, growing children who use backpacks daily may be at risk, especially if they carry an excessive load, which is the norm [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Cottalorda et al [5] reported that no difference was found between carrying a load on one and two shoulders. Symmetrical and asymmetrical school-bag loads did not seem to have any different effect on the gait kinetics of scoliotic children compared to the healthy group in Gelalis et al's study [8]. Pascoe et al [16] and Ozgul et al's [15] studies, however, led to the conclusion that asymmetrical backpack carriage in adolescents biomechanically altered posture and gait parameters.…”
Section: Introductionmentioning
confidence: 89%